In response - Biggar, N (Penn State University Press, 2014)
First of all, let me record my gratitude to colleagues for their having taken the time and trouble to read and comment on my book. Their attention honors it, and their comments serve to test and develop it—sometimes confirming, sometimes correcting, and sometimes identifying further work that remains to be done.